Which men change in intimate partner violence prevention interventions? A trajectory analysis in Rwanda and South Africa - Rachel Jewkes; Nicola J Christofides; Andrew Gibbs; Esnat Chirwa; Kristin Dunkle; Shibe Mhlongo; Abigail Hatcher (BMJ Global Health)
Introduction Emerging evidence suggests working with men to prevent intimate partner violence (IPV) perpetration can be effective. However, it is unknown whether all men benefit equally, or whether different groups of men respond differentially to interventions.Methods We conducted trajectory modelling using longitudinal data from men enrolled in intervention arms of three IPV trials in South Africa and Rwanda to identify trajectories of IPV perpetration. We then use multinomial regression to describe baseline characteristics associated with group allocation.Results In South Africa, the Stepping Stones and Creating Futures (SS-CF) trial had 289 men and the CHANGE trial had 803 men, and in Rwanda, Indashyikirwa had 821 men. We identified three trajectories of IPV perpetration: a low-flat (60%–67% of men), high with large reduction (19%–24%) and high with slight increase (10%–21%). Baseline factors associated men in high-start IPV trajectories, compared with low-flat trajectory, varied by study, but included higher poverty, poorer mental health, greater substance use, younger age and more childhood traumas. Attitudes supportive of IPV were consistently associated with high-start trajectories. In separate models comparing high-reducing to high-increasing trajectories, baseline factors associated with reduced IPV perpetration were depressive symptoms (relative risk ratio, RRR=3.06, p=0.01 SS-CF); living separately from their partner (RRR=2.14, p=0.01 CHANGE); recent employment (RRR=1.85, p=0.04 CHANGE) and lower acceptability of IPV (RRR=0.60, p=0.08 Indashyikirwa). Older aged men had a trend towards reducing IPV perpetration in CHANGE (p=0.06) and younger men in Indashyikirwa (p=0.07).Conclusions Three distinct groups of men differed in their response to IPV prevention interventions. Baseline characteristics of past traumas and current poverty, mental health and gender beliefs predicted trajectory group allocation. The analysis may inform targeting of interventions towards those who have propensity to change or guide how contextual factors may alter intervention effects.Trial registration numbers NCT03022370; NCT02823288; NCT03477877.